Case Report: Intestinal Diverticulum in a Golden Retriever - Emily Eppler; Alyssa Motz (Veterinary Medicine and Science)
ABSTRACT A 1‐year‐old female spayed Golden Retriever presented with a 2‐day history of vomiting and a chronic 4‐month history of intermittent diarrhoea. Blood work revealed hepatocellular hepatopathy with mildly elevated baseline cortisol. Abdominal radiographs revealed mineral opacities in the right caudal abdomen, suspicious for foreign material, but with no evidence of small intestinal obstruction. Owners elected to pursue exploratory laparotomy. A firm, tan, irregular structure was observed in the right caudal abdomen with a small adhesion to an adjacent loop of jejunum. The structure placed caudal tension on a loop of jejunum, causing a hair‐pin turn prior to the beginning of the ileum. The structure was removed en bloc and identified as a focal canine intestinal diverticulum with osseous metaplasia via histopathology.